Karma-Yoga - "Vivekananda, Swami" (Calcutta, 1966)
The classic book on the yoga of action, called karma yoga. All actions have reactions. The trick is to learn how to work in a way that doesn't cause more misery.
Keywords: "Philosophy, Hindu"